2018
DOI: 10.25081/cb.2018.v9.3843
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Epimedium elatum (Morren & Decne) revealed by RAPD characterization

Abstract: Epimedium elatum (Morren & Decne) is a rare perennial monotypic medicinal herb of Berberidaceae family, endemic to high altitude shady coniferous forests of Northwestern Himalayas in India. Traditionally, it has been used in local health care system for treatment of many ailments. In the present study, a total of ten RAPD markers were used for assessment of genetic diversity in twenty accessions of E. elatum, collected from diverse ecozones in Jammu and Kashmir. Ten primers amplified a total of 100 polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Epimedium is clustered into two groups: 1) Mediterranean and Western Asian taxa and 2) East Asian taxa. The present results supported this classification, consistent with the previous studies on the morphology (Stearn 2002), cytology Zhang et al 2018), molecular biology (Kim et al 2004;Guo et al 2018;Sajad et al 2018) and phytochemistry (Guo et al 2008), all of which confirmed the conclusion that the systematic relationship between species is closely related to the specific geographical distribution in this genus. The present results also showed that, although the vast majority of East Asia taxa could be clustered into one group, there are a few species clustered into other groups of Epimedium or the group of Vancouveria, indicating that the genetic diversity of East Asian taxa are the highest in the genus.…”
Section: Relationships Of Epimedium Infrageneric Categories and Speciessupporting
confidence: 93%
“…Epimedium is clustered into two groups: 1) Mediterranean and Western Asian taxa and 2) East Asian taxa. The present results supported this classification, consistent with the previous studies on the morphology (Stearn 2002), cytology Zhang et al 2018), molecular biology (Kim et al 2004;Guo et al 2018;Sajad et al 2018) and phytochemistry (Guo et al 2008), all of which confirmed the conclusion that the systematic relationship between species is closely related to the specific geographical distribution in this genus. The present results also showed that, although the vast majority of East Asia taxa could be clustered into one group, there are a few species clustered into other groups of Epimedium or the group of Vancouveria, indicating that the genetic diversity of East Asian taxa are the highest in the genus.…”
Section: Relationships Of Epimedium Infrageneric Categories and Speciessupporting
confidence: 93%